Outcome of Induction of Labour in Post Dated Pregnancy - Yousuf, NA; Khatan, M (Bangladesh Medical Journal, 2014)
This prospective clinical study was designed on Outcome of induction of labour in post dated pregnancy. A randomized clinical trial was carried out at Sir Salimullah Medical College & Mitford Hospital Dhaka, during the period from November 2002 to June 2003. Sixty post dated pregnant patients, who were chosen for induction, were selected for this study. This study shows that the main method was oxytocin drip and second method was ARM + oxytocin drip, some cases induced by using oral prostaglandin and very few cases induced by intra cervical prostaglandin. 25 patients (65%) were induced by only oxytocin drip and failure rate was 32%, combined ARM and oxytocin drip applied on 25 patient and failure rate was 20%. From this study, it was found that efficacy of combined ARM and oxytocin drip method is superior then the only oxytocin drip method. Therefore combined ARM and oxytocin drip method can be used for induction of labour in post dated pregnancy. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18960 Bangladesh Medical Journal 2012 Vol.41(3): 49-52